Geo-Congress 2014 Technical Papers 2014
DOI: 10.1061/9780784413272.356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fly-Ash-Treated Reclaimed Asphalt Pavement for the Design of Sustainable Pavement Bases: An Indian Perspective

Abstract: Rising costs and scarcity of natural materials such as aggregates are forcing highway agencies to look for alternate pavement designs for new construction, maintenance, and rehabilitation. Several states in USA are currently allowing the use of reclaimed asphalt pavement (RAP) combined with cement for a stabilized base course under both asphalt and concrete pavements. India has very limited experience with recycling and reuse of RAP in various layers of pavement structure. The main objective of the present res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…An evaluation of FA-stabilized RAP as pavement base/sub-base material has been investigated by Saride et al, (2014) whom reported that the Unconfined Compression Strength (UCS) and resilient modulus (M R ) properties can be improved by FA replacement. However, the 7-day UCS of RAP was reported to be lower than the strength requirement specified for pavement base materials.…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of FA-stabilized RAP as pavement base/sub-base material has been investigated by Saride et al, (2014) whom reported that the Unconfined Compression Strength (UCS) and resilient modulus (M R ) properties can be improved by FA replacement. However, the 7-day UCS of RAP was reported to be lower than the strength requirement specified for pavement base materials.…”
Section: Introductionmentioning
confidence: 99%